Hunter's tropical medicine and emerging infections disease - Magill, Alan J.; Hunter, George W. (George William) 1902 (Saunders, 2013)
From infectious diseases through environmental issues, poisoning and toxicology, animal injuries, and nutritional and micronutrient deficiencies, this book provides you with the guidance you need to diagnose and manage even the exotic health concerns.